2005
DOI: 10.1111/j.1365-2672.2005.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio splendidus biotype 1 as a cause of mortalities in hatchery-reared larval turbot, Scophthalmus maximus (L.)

Abstract: Aims: To characterize bacteria associated with turbot larvae feeding on Artemia and identify pathogens causing mortalities in larvae. Methods and Results: To identify bacteria associated with mortalities in larval turbot rearing, bacteria were isolated from homogenates of Artemia or from several batches of well-performing or poorly performing turbot larvae. Samples were plated onto marine agar and were characterized using biochemical tests and BIOLOG GN plates. Total culturable aerobic bacteria ranged from 1AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…It is known to be a problem in the farming of salmonid fish, especially the salmon Salmo salar, but little information is available concerning V. salmonicida in marine fish species (reviewed by Bricknell et al 2006). V. splendidus has been described as being pathogenic to fish (Thomson et al 2005, Bergh & Samuelsen 2007) and bivalves (Gómez-León et al 2005, Sandlund et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be a problem in the farming of salmonid fish, especially the salmon Salmo salar, but little information is available concerning V. salmonicida in marine fish species (reviewed by Bricknell et al 2006). V. splendidus has been described as being pathogenic to fish (Thomson et al 2005, Bergh & Samuelsen 2007) and bivalves (Gómez-León et al 2005, Sandlund et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have determined that vibrios can be found in microaggregates , biofilms (Kwon et al, 2002), sediments (Kopke et al, 2005), associated with marine animals and macroalgae Thomson et al, 2005) and within the water column. Vibrios are amenable to multilocus sequencing because they can be isolated on selective media from the environment and grown in culture.…”
Section: Goals Of This Thesismentioning
confidence: 99%
“…Fish pathogens Listonella anguillarum (Bergeman, 1909;MacDonell & Colwell, 1986) and Vibrio splendidus (Beijerinck, 1900) have been found to be associated with live prey (Thomson et al, 2005), causing mortality to fish larvae (Thomson et al, 2005;Reid et al, 2009). The strains L. anguillarum and V. splendidus are pathogenic to turbot larvae but the infection patterns for both species seem to be different.…”
Section: Introductionmentioning
confidence: 99%
“…The strains L. anguillarum and V. splendidus are pathogenic to turbot larvae but the infection patterns for both species seem to be different. V. splendidus was detected and isolated from the gut of diseased turbot larvae (Thomson et al, 2005;Reid et al, 2009) whereas L. anguillarum was found in the epidermis of experimentally infected turbot larvae (Planas et al, 2005). Considering this, bacterial infection present in aquaculture systems is an important problem that must be controlled and strict biosecurity measures must be implemented to avoid introduction of contaminated food to fish.…”
Section: Introductionmentioning
confidence: 99%